(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2011)
Carding is an important step in processing line of jute spinning. A cylinder is the heart of the whole carding machine due to the carding action, which causes from its cylinder speed and other rollers. This action occurs in breaker card and finisher card machine. This study was carried out to find out the effectiveness of various delivery roller speeds of finisher card cylinder on quality of jute-blended yarn 275 tex (8 lbs/spy). An assessment of the quality of 275 tex (8 lbs/spy) yarns spun from the 100% raw jute and jute acrylic blend were made in terms of their physical properties. The results were compared with those of the 100% jute yarns. Raw jute was blended with acrylic and their blended yarns were manufactured mainly to take advantage of value addition and to produce better yarn of jute fibre. For spinning jute acrylic blended yarn, jute fibre was mixed with acrylic in the ratio of 80% jute and 20% acrylic. Medium delivery roller speed (1830 inch/min) of the finisher card cylinder is better than any other speeds for good quality of jute blended yarn. The physical properties of the produced yarns such as load at break, strain percentage, tenacity at break, textile modulus, and quality ratio were tested. Some empirical relations have been developed between the processing parameters of the machine and physical properties of the yarn. The developed equations are valid within the experimental region. Key words: Carding; Spinning; Cylinder; Speed; Quality; Jute yarn DOI: http://dx.doi.org/10.3329/bjsir.v46i3.9034 BJSIR 2011; 46(3): 303-306